Advanced Control Systems for Axial Piston Pumps Enhancing Variable Mechanisms and Robust Piston Positioning - Feng, Yuan; Jian, Zhang; Li, Jiayang; Tao, Zhang; Wang, Yuhang; Xue, Jingwei (Applied sciences, 2023)
Axial piston pumps provide a number of benefits, including strong pressure resistance, high efficiency, high transmission power, a broad speed range, and a long lifespan. These characteristics have led to their widespread usage in naval applications, construction machines, and hydraulic machinery. On the other hand, axial piston pumps frequently display reduced operating speeds as well as instability because of their inherently nonlinear properties. In this study, a mathematical model of these changeable (variable) processes is developed using a mix of theoretical calculations and acquired data. An investigation of variable mechanism control in axial piston pumps is carried out centered on robust control methods, and the controller is constructed utilizing robust H∞ theory. In terms of resilience, control precision, and system reaction time, simulations show that the H controller surpasses the PID controller.